Pengaruh Pemberian Lidokain 2% sebelum Ekstubasi terhadap Penurunan Kejadian Batuk saat Proses Ekstubasi - Suryaningrat, IGB; Bisri, Tatang; Oktaliansah, Ezra (Perdatin Pusat, 2014)
Batuk saat ekstubasi pada pasien dengan anestesi umum dan endotrakeal merupakan masalah klinis yang dihadapi. Angka kejadian berkisar 38%−96%. Pemberian lidokain sebelum ekstubasi secara laringotracheal instilation of topical anesthesia endotracheal tube (ETT LITA) dapat mengurangi kejadian batuk saat ekstubasi. Tujuan penelitian adalah menilai efek pemberian lidokain 2% 1,25 mg/kgBB endotrakeal sebelum ekstubasi terhadap kejadian batuk saat ekstubasi. Penelitian kuantitatif intervensi dengan uji klinis acak terkontrol buta tunggal dengan subjek penelitian: 50 pasien laki-laki, usia 18−60 tahun, status fisik American Society of Anesthesiologists I dan II, operasi elektif dengan endotrakeal. Subjek dibagi menjadi 2 kelompok, yaitu kelompok I yang mendapat lidokain 2% 1,25 mg/kgBB endotrakeal 5 menit sebelum ekstubasi dan kelompok kontrol yang tanpa perlakuan. Data diuji dengan uji chi-kuadrat dan uji t. Penelitian dilakukan periode Februari−April 2014 di Rumah Sakit Dr. Hasan Sadikin Bandung. Kejadian batuk rata-rata saat ekstubasi pada kelompok lidokain lebih rendah dibanding dengan kelompok kontrol dengan hasil yang bermakna (p<0,05). Derajat batuk 5 menit pascaekstubasi antara kedua kelompok menunjukkan berbeda bermakna (p=0,00046). Simpulan penelitian ini menunjukkan bahwa pemberian lidokain 2% 1,25 mg/kgBB endotrakeal sebelum ekstubasi dapat menurunkan kejadian batuk saat ekstubasi. Kata kunci: Anestesi umum, batuk, ekstubasi, lidokain endotrakeal Cough during extubation under general anesthesia with endotracheal intubation is a clinical problem that encountered. The Incidence rates ranged from 38%−96%. Lidocaine spray given before extubation through instillation process into the laringotracheal instilation of topical anesthesia endotracheal tube (ETT LITA) significantly lower the incidence of coughing during extubation. The goal of this research is to see the effect of lidocaine 2%, 1,25 mg/kgbw through endotracheal before extubation toward cough incidence during extubation of endotracheal tube process. In our prospective, single-blind randomized controlled clinical trial, we enrolled 50 male patients aged 18−60 years, ASA physical status I and II underwent elective surgery with generalwith endotracheal tube insertion. The subject was then divided into 2 groups, first group had lidocaine 2% 1,25 mg/kgBW endotracheal 5 minute before extubation and the control group without any intervention. The data result was tested statistically with chi-square and t-test. This study was conducted from February ̶ April 2014 in the operating room Dr. Hasan Sadikin Hospital, Bandung.Tthe statistic result, cough incidence was found at extubation process in the group that had lidocain 2% 1.25 mg/kgbw is lower than control group with significant result (p<0.05). the cough degree 5 minutes post extubation in the grup that had lidocain 2% 1.25 mg/kgbw compare to control group in significantly different (p=0.00046). The conclusion is shows lidocaine 2% 1.25 mg/kgbw effect through endotracheal before extubation significantly lower cough incidence throughout extubation process. Key words: Cough, endotracheal lidocaine, extubation, general anesthesia Reference Minogue SC, Ralph J, Lampa MJ. Laryngotracheal topicalization with lidocaine before intubation decreases the incidence of coughing on emergence from general anesthesia. Anesth Analg. 2004;99:1253−7. Jee D, Park SY. Lidocaine sprayed down the endotracheal tube attennuates the airwaycirculatory reflexes by local anesthesia during emergence and extubation. Anesth Analg. 2003;96(1):293−7. Ki YM, Kim NS, Lim SH, Kong MH, Kim HZ. The effect of lidocaine spray before endotracheal intubation on the incidence of cough and hemodynamics during emergence in children. Korean J Anesthesiol .2007;53:1−6. Morgan EG, Mikhail MS, Murray MJ. Management airway. Dalam: Morgan EG, Mikhail MS, Murray MJ, penyunting. Clinical anesthesiology. Edisi ke-4. New York: McGraw-Hill;2006. Hlm. 91−116. Henderson J. Airway management in adult. Dalam: Miller RD, penyunting. Miller’s Anesthesia. Edisi ke-7. Philadelphia: Elsevier Churcill Livingstone; 2010. Hlm.1573−610. Karmarkar S, Varshney S. Tracheal extubation. Continuing education in anaesthesia, Crit are & Pain 2008;8(6):214−20 Gonzalez RM, Bjerke RJ, Drobycki T. Prevention of endotracheal tube-induced coughing during emergence from general anesthesia. Anesth Analg. 1994;79:792−5. Diachun CD, Tunink BP, Brock-Utne JG. Suppression of cough during emergence from general anesthesia: laryngotracheal lidocaine through a modified endotracheal tube. J Clin Anesth 2001;13:447−57 Nishino T, Hiraga K, Sugimori K. Effects of intravena lignocaine on airway reflexes elicited by irritation of the tracheal mucosa in humans anesthetized with enflurane. Br J Anaesth. 1990;64:682−7. Hamaya Y, Dohi S. Differences in cardiovascular response to airway stimulation at different sites and blockade of responses by lidocaine. Anesthesiol.2000;93(1):95−103 Orandi AN, Hajimohammadi F. Post-Intubation Sore Throat and Menstrual Cycles. Anesth Pain. 2013;3(2):243−9. Liu J, Zhang X, Gong W, Li S, Wang F, FuS, dkk. Correlations between Controlled endotracheal tube pressure and postprocedural comploication: a multicenter study. Anesth Analg 2010;111;1133−7 Jaicbandran VV, Bhanulaksmi IM, Jagadeesh V. Intracuff buffered lidocaine versus saline or air-A comparati.v.e study for smooth extubation in patients with hyperactive airways undergoing eye surgery. SAJAA .2009;15(2):114 Navarro LHC, Lima RM, Aguiar AS, Braz JR, Carness JM, Modolo NS. The effect of intracuff alkalinized 2% lidocaine on emergence coughing, sore throat, and hoarseness in smokers. Rev Assoc Med Bras. 2012;58(2):248−53. Canning BJ. Anatomy and neurophysiology of the cough reflex. Chest. 2006;129:Suppl:33−47. Widdicombe JG. A brief overview of the mechanisms of cough. Dalam: Chung KF, Widdicombe JG, Boushey HA, penyunting. Cough: Causes, mechanism and therapy. Massachusetts: Blackwell Publishing: 2003.hlm.17−25.